GROWING FAST AND PROFITABLY IN THE HIGHLY COMPETITIVE TELECOM INDUSTRY: THE CASE OF GVT - Bruno Henrique Rocha Fernandes (Administração: Ensino e Pesquisa, 2018)
The purpose of this teaching case is to study the remarkable history of GVT, the former Brazilian telecom company which was acquired by Telefónica Vivo after it had revolutionized the telecom industry in Brazil throughout its 15 years of operation. Telecommunications is an industrial sector that is constantly undergoing upheavals, owing to the rapid pace of technological innovation, as well as the fierce competition, that forces companies to redesign their business models in order to flourish. This case is aimed at Master´s and Doctorate students doing courses in Business Administration, and should also be a useful way of helping teachers/lecturers to discuss business models in a dynamic class environment, such as in the area of the telecom industry. The learning objectives are to enable the participants to understand the features and limitations of the traditional concepts of business models, and to set out guidelines for an alternative framework that is suitable for a dynamic environment. The teachers involved should cover the aspects of differentiation strategies, consistent execution, process management and learning capabilities.